Remote Labs Accessible through 3D environments: A Case Study with Open Wonderland - Costa, David T. (2017)
3D immersive environments have been spreading through domains such as enterprise activities, education and entertaining, due to the Second Life growth. This and other 3D environments can be used to increase the sense of immersion of users accessing remote laboratories, namely when controlling & observing measuring instruments. This paper contributes to the overall research efforts, on this domain, by presenting a case study of how to remotely access a digital multimeter, through a 3D environment developed in Open Wonderland.